Engineering heat transfer - Rathore, M. M (Mahesh M.) (Jones and Bartlett Learning, 2011)
This book is designed as a basic text for undergraduate courses in heat transfer for students of mechanical, chemical, aeronautical, and metallurgical engineering, or as a reference for professionals in industry. Treating each subject analytically and then numerically, Engineering Heat Transfer emphasizes the clear understanding of theoretical concepts followed by practical applications from industry. It also provides step-by-step solutions of numerical problems through the use of systematic procedures and a prescribed format. This book also includes discussions on how to develop programs that solve heat transfer problems using MATLAB. MATLAB provides a higher-level programming environment, which allows the user to rapidly develop programs that involve complex numerical and engineering heat transfer computations.